(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we present complex valued controlled S-metric spaces, a new generalisation of controlled S-metric spaces. This generalization is also a new extension of the notion of a complex valued S_b-metric space, which differs from the complex valued extended S_b-metric space. Moreover, in this newly generalized notion, we derive certain fixed point results along with an example. Many results from the existing literature are also derived as corollaries of our main results. As an application of our result, we demonstrate the existence of a solution of a Volterra integral equation.